2011
DOI: 10.1162/jocn.2010.21487
|View full text |Cite
|
Sign up to set email alerts
|

Level of Processing Modulates the Neural Correlates of Emotional Memory Formation

Abstract: Emotion is known to influence multiple aspects of memory formation, including the initial encoding of the memory trace and its consolidation over time. However, the neural mechanisms whereby emotion impacts memory encoding remain largely unexplored. The present study employed a levels-of-processing manipulation to characterize the impact of emotion on encoding with and without the influence of elaborative processes. Participants viewed emotionally negative, neutral, and positive scenes under two conditions: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
61
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 49 publications
6
61
0
2
Order By: Relevance
“…2) (Dolcos et al, 2004b). Neuroimaging evidence also revealed that the increased AMY activation during memory formation may depend on the level-of processing during encoding (Ritchey, Labar, & Cabeza, 2011) and be related to the subjective vividness of subsequent memory regardless of arousal and valence (Kensinger, Addis, & Atapattu, 2011). The latter finding suggests that AMY's involvement may not be always a sign of encoding more details but rather seems to correspond to the subjective feeling of vivid memory.…”
Section: Neural Correlates Of the Memory-enhancing Effect Of Emotion mentioning
confidence: 94%
See 3 more Smart Citations
“…2) (Dolcos et al, 2004b). Neuroimaging evidence also revealed that the increased AMY activation during memory formation may depend on the level-of processing during encoding (Ritchey, Labar, & Cabeza, 2011) and be related to the subjective vividness of subsequent memory regardless of arousal and valence (Kensinger, Addis, & Atapattu, 2011). The latter finding suggests that AMY's involvement may not be always a sign of encoding more details but rather seems to correspond to the subjective feeling of vivid memory.…”
Section: Neural Correlates Of the Memory-enhancing Effect Of Emotion mentioning
confidence: 94%
“…This manipulation revealed that the AMY-MTL connectivity during encoding was greater for items retrieved after a longer delay, thus suggesting that AMY-MTL interactions underlie consolidation and persistence of emotional memories over time. Recent evidence also shows that although activity in AMY and MTL is driven primarily by arousal, their interaction may depend on valence (Ritchey et al, 2011). Namely, the study by Ritchey et al (2011) showed that the AMY-MTL interaction was stronger for encoding of negative stimuli, while the interaction between MTL and prefrontal cortex (PFC) was stronger for encoding of positive stimuli (see below.…”
Section: Neural Correlates Of the Memory-enhancing Effect Of Emotion mentioning
confidence: 99%
See 2 more Smart Citations
“…Processing of emotionally laden memories has been associated with unique neural (Ritchey et al, 2011) and autonomic nervous system responses (Buchanan and Lovallo, 2001;Cahill and McGaugh, 1998;Garcia et al, 2011;Schwabe et al, 2008). These distinct brain and body responses to emotional stimuli result, at least in part, from the plicit memory).…”
mentioning
confidence: 99%